Vincristine, aspirin, and prednisolone therapy in Kasabach-Merritt phenomenon: Response in 2 cases - Shikha Gupta; Subhash Bharti; Niyaz Ahmed Khan; Lavleen Singh (Wolters Kluwer Medknow Publications, 2019)
Kasabach-Merritt phenomenon (KMP) is a severe thrombocytopenic coagulopathy which usually occurs in the presence of enlarging vascular tumors such as kaposiform hemangioendothelioma (KHE) and tufted angioma. The treatment for this potentially fatal condition is challenging without a consensus on appropriate management. The authors report two cases of KHE with KMP, wherein improvement in size of tumor and coagulopathy occurred after treatment with prednisolone, vincristine, and aspirin.